DNMT1 Inhibitor Restores RUNX2 Expression and Mineralization in Periodontal Ligament Cells - Assis, Rahyza I. F.; Schmidt, Arthur G.; Racca, Francesca; Silva, Rodrigo A. da; Zambuzzi, William F. [UNESP]; Silverio, Karina G.; Nociti, Francisco H.; Pecorari, Vanessa G.; Wiench, Malgorzata; Andia, Denise C. (Mary Ann Liebert, Inc, 2021)
Periodontal ligament cells (PDLCs) have well documented osteogenic potential; however, this commitment can be highly heterogenous, limiting their applications in tissue regeneration. In this study, we use PDLC populations characterized by high and low osteogenic potential (h-PDLCs and l-PDLCs, respectively) to identify possible sources of such heterogeneity and to investigate whether the osteogenic differentiation can be enhanced by epigenetic modulation. In h-PDLCs, low basal expression levels of pluripotency markers (NANOG, OCT4), DNA methyltransferases (DNMT1, DNMT3B), and enzymes involved in active DNA demethylation (TET1, TET3) were prerequisite to high osteogenic potential. Furthermore, these genes were downregulated upon early osteogenesis, possibly allowing for the increase in expression of the key osteogenic transcription factors, Runt-related transcription factor 2 (RUNX2) and SP7, and ultimately, mineral nodule formation. l-PDLCs appeared locked in the multipotent state and this was further enhanced upon early osteogenic stimulation, correlating with low RUNX2 expression and impaired mineralization. Further upregulation of DNMTs was also evident, while pretreatment with RG108, the DNMTs' inhibitor, enhanced the osteogenic program in l-PDLCs through downregulation of DNMTs, increased RUNX2 expression and nuclear localization, accelerated expression of osteogenic markers, and increased mineralization. These findings point toward the role of DNMTs and Ten Eleven Translocations (TETs) in osteogenic commitment and support application of epigenetic approaches to modulate biomineralization in PDLCs.
Keywords: periodontal ligament stem cells; osteogenic potential; RUNX2; DNA methyltransferases; RG108